Concordance of Identified Cases of Pediatric HA-VTE with American College of Physicians and Cincinnati Children's Hospital HA-VTE Prophylaxis Guidelines Over a 10-Year Period - Elaine M. Fan MD; Deirdre Lewis MD; Thomas Presti MD; Nura El-Haj MD; Weijen W. Chang MD, SFHM FAAP (SAGE Publishing, 2020)
Objective : Our aim is to (1) ascertain the proportion of pediatric patients at a tertiary hospital in Western Massachusetts over a 10-year period with hospital-acquired venous thromboembolism (VTE) of particular characteristics and (2) determine whether ACCP or Cincinnati Children's guidelines would have recommended VTE prophylaxis in these patients. Setting : Urban teaching hospital in the United States. Participants : Data from 98 477 pediatric hospital admissions (roughly 10 000 admission per year) from 2008 to 2017 were reviewed. There were a total of 177 VTE cases identified. Outcome measures : Hospital-acquired venous thromboembolism (including deep venous thrombosis and pulmonary embolism). Result : 177 charts were extracted that carried the diagnosis of VTE based on ICD-9 and ICD-10 codes over a 10-year-period. Among these patients, 34 (19%) met the inclusion criteria for HA-VTE; 5 (16%) would qualify for prophylaxis according to ACCP and 7 (21%) according to Cincinnati Children's guideline. The most common age group to have a VTE was infants under 1 year of age (41%), and the most common characteristic was the presence of a central line (82%). Age outside of the recommended range was the sole reason that excluded patients from prophylaxis qualification per Cincinnati Children's. Conclusion : HA-VTE carries increased morbidity and mortality. Although recognition and prevention of HA-VTE in adult populations are routine, prophylaxis for pediatric HA-VTE is not commonly practiced. This may be due to paucity of strong evidence supporting prophylaxis and the challenge of identifying risk factors for HA-VTE. Our results suggest that published guidelines recommend prophylaxis in only a minority of pediatric patients who would have subsequently developed HA-VTE. Further modification and validation of current guidelines are needed to effectively prevent pediatric HA-VTE.